Direct synthesis of self-pillared zeolite nanosheets by repetitive branching. - Thommes, Matthias; et al. (Abstracts of Papers, 244th ACS National Meeting & Exposition, Philadelphia, PA, United States, August 19-23, 2012, 2012)
The synthesis of a new hierarchical zeolite, self-pillared pentasil (SPP), with intersecting microporous 2 nm-thick lamellae was demonstrated. The lamellae have the microporous structure of zeolite MFI and by repetitive twinning grow in a house-of-cards arrangement (i.e., with the lamellae arranged perpendicular to each other, to define pores between them) leading to hierarchical micro/mesoporosity. Unlike other hierarchical zeolites, SPP is made by one-step hydrothermal synthesis using a simple and inexpensive structure-directing agent. The crystal growth mode involving repetitive branching is a new approach toward hierarchical materials with interconnected micro and mesopores. Its catalytic properties follow behavior that can be quant. described by classical reaction-diffusion models. The high external surface area and reduced micropore diffusion length of zeolite nanosheets account for higher reaction rates for bulky mols. compared to those of other mesoporous and conventional MFI zeolites. [on SciFinder(R)]